Hubungan Mencuci Tangan dan Perawatan Kuku dengan Kejadian Helmintiasis pada Siswa/i Sekolah Dasar - Lestari, Kustiasih; Melly; Elisanov, Virpy; Agritubella, Syafrisar Meri (Poltekkes Kemenkes Kupang, 2022)
Introductions: Helminthiasis is a worm infection that often attacks children to adults. A quarter of the world’s population suffers from Soil-Transmitted Helminthes (STH). Various problems arising from worm infection include changes in appetite, nausea, vomiting, and weight loss. In children, it can inhibit growth and development. The purpose was to identify handwashing behaviour, nail hygiene and incidence of Helminthiasis in Elementary School students. Methods: This is quantitative research with a cross-sectional study to link hand washing and nail hygiene with worms in students with 106 respondents. Examination of faecal preparations was carried out at the Thamrin Laboratory. Result: The results obtained were 14 people (13,2%) with hand washing behaviour in the poor category, 14 people (13,2%) with nail hygiene in the poor category, and 14 people (13,2%) have worm infection. Based on bivariate analysis, p-value=0.000 (5%), Conclusion: There is a relationship between hand washing behaviour and nail hygiene with the incidence of worms in students of Elementary School.